All Days 2012
DOI: 10.2118/163279-ms
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Organically Crosslinked Polymer for Water Shutoff in High-Temperature Well Applications

Abstract: Excessive water production from unwanted zones in oil producing wells is one of the major challenges faced by the oil industry. The applicability of organically crosslinked polymer (OCP) systems as sealants for water shutoff treatments in temperatures up to 350°F is well documented. However, their effectiveness at temperatures above 350°F has not been evaluated. This paper presents experimental data from using an OCP system for water shutoff treatments at 400°F.At temperatures around 400°F, crosslinking is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This indicates that the deployment of the organic polymeric gel system at high‐temperature reservoirs without gelation retarding agent is a difficult task. Hence, the retarders are essential to elongate the gelation time, slow down the hydrolysis, and strengthen the gel …”
Section: Factors That Affect Gelation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the deployment of the organic polymeric gel system at high‐temperature reservoirs without gelation retarding agent is a difficult task. Hence, the retarders are essential to elongate the gelation time, slow down the hydrolysis, and strengthen the gel …”
Section: Factors That Affect Gelation Kineticsmentioning
confidence: 99%
“…After doing a sandpack flow test, Eoff et al found that the addition of this salt as a retarder could raise the working temperature without affecting the gel strength and its subsequent ability to stop fluid flow . Although Na 2 CO was found to have an excellent retardation effect for the PAtBA/PEI system, it has disadvantages and compatibility problems with in high salinity brines . The use of salts as retarder can bring negative impact if the compatibility with the field mixing brines is not carefully assessed.…”
Section: Factors That Affect Gelation Kineticsmentioning
confidence: 99%